2019
DOI: 10.22207/jpam.13.2.58
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic Diagnostic Tool based on Chip Mini RT-PCR for Diagnosis of Pulmonary and Extra Pulmonary Tuberculosis

Abstract: Diagnosis of Tuberculosis (TB) is a challenging problem with the currently available conventional methods such as microscopy for Acid Fast Bacilli (AFB) and culture techniques.The diagnosis of Extra pulmonary tuberculosis (EPTB) is still more challenging due to the low yield of bacilli in the clinical specimens. Recently, a chip based Reverse Transcriptase Polymerase Chain Reaction (RT-PCR) was introduced in India. This study was conducted for finding out the sensitivity and specificity of TrueNAT RT-PCR for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Ltd. (Bangalore, India) developed three assays that utilize chip-based real-time micro PCR, two for detection of M. tuberculosis: the Truenat™ MTB (including the nrdB single copy target) and MTB Plus (including nrdZ and multi-copy IS6110 targets) assays; and one for the detection of RIF resistance: the MTB-RIF Dx reflex assay targeting the rpoB gene [11,12]. These assays can be run from the same DNA eluate [13][14][15][16], obtained from the automated bead-based Trueprep ® DNA extraction device that uses a universal cartridge-based system to extract DNA from 0.5 mL of sputum in under 20 minutes. The DNA eluate is loaded onto the chipbased Truelab ™ micro PCR device to detect the presence of M. tuberculosis DNA in approximately 40 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…Ltd. (Bangalore, India) developed three assays that utilize chip-based real-time micro PCR, two for detection of M. tuberculosis: the Truenat™ MTB (including the nrdB single copy target) and MTB Plus (including nrdZ and multi-copy IS6110 targets) assays; and one for the detection of RIF resistance: the MTB-RIF Dx reflex assay targeting the rpoB gene [11,12]. These assays can be run from the same DNA eluate [13][14][15][16], obtained from the automated bead-based Trueprep ® DNA extraction device that uses a universal cartridge-based system to extract DNA from 0.5 mL of sputum in under 20 minutes. The DNA eluate is loaded onto the chipbased Truelab ™ micro PCR device to detect the presence of M. tuberculosis DNA in approximately 40 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…A better technique for diagnosis can be rapid, accurate and highly sensitive. RT-PCR has been proven to be the more useful molecular technique to diagnose pulmonary and extra-pulmonary TB due to the efficient processing of fluid and tissue samples of patients (Mangayarkarasi, et al, 2019). The Positivity rate in pulmonary samples is much higher in the case of Real-Time PCR Technique which is 44.44% when compared to Fast Plaque Assay which is 13.33% which tells that the Real-Time PCR Technique is a much better technique than Fast Plaque Assay.…”
Section: Resultsmentioning
confidence: 99%
“…Up to date, the diagnosis of tuberculosis is still a challenge in the clinical medicine by using available conventional methods and it is more difficult to detect extra pulmonary tuberculosis (EPTB) due to the low yield of bacilli in the clinical specimens. For the purpose of addressing this challenge, a chip based TrueNAT device using RT-PCR was introduced for the diagnosis of pulmonary tuberculosis (PTB) and EPTB [454] . A systematic evaluation of the device was conducted using a total of 145 clinical samples including both PTB (80) and EPTB (65).…”
Section: Poc Devices For Infectious Disease Detectionmentioning
confidence: 99%
“…All the results demonstrated that the sensitivity and specificity of TrueNAT device is 93.1% and 72.5% for the diagnosis of PTB and 96.77% and 76.4% for EPTB, respectively. Besides, the device was able to achieve fast detection of PTB and EPTB as well as rifampicin resistance within 2 h, which is portable and compatible for POC detection of Mycobacterium tuberculosis [454] . Moreover, an integrated continuous flow PCR (CF-PCR) and electrophoresis biochip based all-in-one microfluidic device was recently developed by Li and his coworkers for the detection of Porphyromonas gingivalis , Treponema denticola and Tannerella forsythia [455] .…”
Section: Poc Devices For Infectious Disease Detectionmentioning
confidence: 99%